SHMT inhibitor synergizes with 5-Fu to suppress gastric cancer via cell cycle arrest and chemoresistance alleviation - Huan Deng; Yajie Wang; Lin Xiao; Mei Feng; Weidong Dou; Yisheng Pan (npj Precision Oncology)
Abstract Advanced gastric cancer (GC) represents a malignancy tumor with poor prognosis, which requires urgent exploration into its molecular drivers and innovative therapeutic strategies. This study investigates the oncogenic role of serine hydroxymethyltransferase isoforms (SHMT1/SHMT2), key regulators of serine-glycine-one-carbon metabolism, in GC progression and chemoresistanc. Bioinformatics analysis and cytological experiments preliminary identified the important role of SHMTs in GC. Drug synergistic screening assays were used to build the therapeutic model in the study. The transcriptomic analysis was performed to clarify the underlying mechanism of combination treatment. Our investigations demonstrate that SHMT1 and SHMT2 functionally drive malignant progression and confer 5-fluorouracil (5-Fu) resistance in GC, while their selective inhibitor SHIN1 emerges as a novel therapeutic candidate for GC treatment. The synergistic screening analysis showed that SHIN1 was an efficient synergist for 5-Fu, and the combinative therapy amplified their anticancer effects. Mechanistically, the combination treatment induced cell cycle arrest, DNA damage and cellular senescence by regulating the P53 signaling pathway. These unique characteristics of cell cycle arrest through interfering nucleotide synthesis were validated by substantial in vitro and in vivo assays. The present study revealed SHMT isforms as the potential promoter for malignant progression and chemoresistance in GC. The inhibitor SHIN1 alleviates chemoresistance of 5-Fu and augments both therapeutic effects on GC. In conclusion, the combination of SHIN1 with 5-Fu represents a promising preclinical model for GC treatment, offering a novel strategy to overcome drug resistance and improve therapeutic efficacy.